46,XY DSD WITH HETEROZYGOUS MUTATION IN THE NR5A1 GENE: A CASE REPORT - Hooi, Ong Kah; Selveindran, Nalini; Balakrishnan, Jayagauri; Hua, Janet Hong Yeow (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Disorders of Sexual Development ( DSD ) is a rare disorder with a wide variable phenotype. These conditions occur rarely with a prevalence of about 1 per 5000 live births. Despite advances in genetic diagnostics, the underlying genetic cause in many of these patients remains elusive. One genetic cause for DSD, especially in individuals with 46,XY karyotype, is mutations in the NR5A1 (Nuclear receptor subfamily 5, group A, member 1) gene. NR5A1 encodes the transcription factor Steroidogenic Factor-1 (SF1) that plays a pivotal role in adrenal and gonadal development as well as in steroidogenesis. SF-1 is expressed in the bipotential gonad and regulates its differentiation towards testes and ovaries CASE A 4-year-old child presented at birth with ambiguous genitalia. There was significant ambiguity of the genitalia presenting as micropenis (stretched penile length: 1.4cm), perineal hypospadias, bifid scrotum with bilateral descended testis in the scrotum. Initial investigations revealed chromosomal study of 46,XY, normal adrenal response on the ACTH stimulation test and an appropriate gonadotrophin surge during minipuberty. Beta HCG stimulation test revealed a poor testosterone response and the antimullerian hormone results were normal. Ultrasound of the pelvis and abdomen showed bilateral testes seen within the scrotal sacs and no Mullerian structures. Gender was subsequently decided as male following discussion with parents. Subsequently blood was sent for whole exome sequencing (WES) which revealed a heterozygous variant in NR5A1 gene. CONCLUSION In conclusion, we report a patient with 46,XY DSD with a heterozygous mutation in the NR5A1 gene. Patients with NR5A1 mutations regardless of phenotype at birth, may demonstrate considerable virilization at puberty. Therefore, it is important to consider gender assignment carefully in all patients.